Value of Pre-Operative Planning with Selecting the Most Functional Vessels by Ultrasound Vascular Mapping of Upper Limb for Haemodialysis Access Placement - Lekhyasree, Pabbu; Baru, Ramakrishna Rao (Asian Journal of Medical Radiological Research, 2022)
Background: The increasing prevalence of end-stage renal illness, as well as its influence on health-care costs, has led in a greater emphasis on the provision of vascular access treatment. USG is an effective modality for evaluating (Haemodialysis) HD access since it is quick, easy to use, non-invasive, and affordable. With the advancement of high resolution USG machines, Now it is feasible to gather data prior surgery, assisting in surgery planning. This study aimed to find the value of pre-operative planning with choosing the most functional vessels through mapping of the upper extremity by ultrasound for HD access creation, with the subsequent reduction in morbidity and hospitality cost after AV fistula placement. The objective of study is identifying correlation between Doppler USG findings and operational results (as assessed by anatomy, vessel size, patency, and wall morphology). Subjects and Methods: This research comprised 35 patients who were referred from Narayana Medical College’s urology and nephrology departments for HD creation. The research took place between November 2019 and November 2021. The doppler results were then compared to the surgery findings and outcome. Doppler vessel sizes and per operative surgical results of vessel diameter were recorded and compared to identify differences. The correlation was used to identify access points selected and the type of access executed. The disparities discovered between US and operative results were also analyzed. Results: The findings of doppler USG were strongly correlated with operative findings. 94.2% accuracy is detected with preoperative Doppler USG for choosing potential sites for Hemodialysis access creation. 85.7% rise in AVF creation is observed When a physical examination is combined with Doppler USG. Summary: In this research, upper extremity vessels were sonographic ally assessed in 35 patients before AVF creation based on standard criteria & potential access sites were selected. Main purpose of this research was to determine the value of pre-operative planning with choosing the most functional vessels by ultrasound vascular mapping of the upper extremity for hemodialysis access placement, resulting in a reduction in morbidity, hospitality cost after AV fistula placement. The findings of Doppler USG were strongly correlated with operative findings. Conclusion: In patients whose physical examination was indeterminate, preoperative vascular mapping by Doppler USG by using various parameters such as vessel diameter, wall morphology, peak systolic flow, Spectral wave from, anatomical course, patency, depth from skin surface helped a lot in choosing potential sites for access creation.